Genome-Wide Methylation Profiling of lncRNAs Reveals a Novel Progression-Related and Prognostic Marker for Colorectal Cancer - Lin, Shujuan; Gu, Simeng; Qian, Sangni; Liu, Yaxin; Sheng, Jinghao; Li, Qilong; Yang, Jinhua; Ying, Xiaojiang; Li, Zhenjun; Tang, Mengling; Wang, Jianbing; Chen, Kun; et al. (Frontiers in Oncology, 2022)
Sporadic colorectal cancer (CRC) develops principally through the adenoma-carcinoma sequence. Previous studies revealed that DNA methylation alteration play a significant role in colorectal neoplastic transformation. On the other hand, long noncoding RNAs (lncRNAs) has been identified to be associated with some critical tumorigenic processes of CRC. Accumulating evidence indicates more intricate regulatory relationships between DNA methylation and lncRNAs in CRC. Nevertheless, the methylation alterations of lncRNAs at different stages of colorectal carcinogenesis based on a genome-wide scale remain elusive. Therefore, in this study, we first used an Illumina MethylationEPIC BeadChip (850K array) to identify the methylation status of lncRNAs in 12 pairs of colorectal cancerous and adjacent normal tissues from cohort I, followed by cross-validation with The Cancer Genome Atlas (TCGA) database and the Gene Expression Omnibus (GEO) database. Then, the abnormal hypermethylation of candidate genes in colorectal lesions was successfully confirmed by MassARRAY EpiTYPER in cohort II including 48 CRC patients, and cohort III including 286 CRC patients, 81 advanced adenoma (AA) patients and 81 nonadvanced adenoma (NAA) patients. DLX6-AS1 hypermethylation was detected at all stages of colorectal neoplasms and occurred as early as the NAA stage during colorectal neoplastic progression. The methylation levels were significantly higher in the comparisons of CRC vs. NAA (P < 0.001) and AA vs. NAA (P = 0.004). Moreover, the hypermethylation DLX6-AS1 promoter was also found in cell-free DNA samples collected from CRC patients as compared to healthy controls (Padj = 0.003). Multivariate Cox proportional hazards regression analysis revealed DLX6-AS1 promoter hypermethylation was independently associated with poorer disease-specific survival (HR = 2.52, 95% CI: 1.35-4.69, P = 0.004) and overall survival (HR = 1.64, 95% CI: 1.02-2.64, P = 0.042) in CRC patients. Finally, a nomogram was constructed and verified by a calibration curve to predict the survival probability of individual CRC patients (C-index: 0.789). Our findings indicate DLX6-AS1 hypermethylation might be an early event during colorectal carcinogenesis and has the potential to be a novel biomarker for CRC progression and prognosis.